2014
DOI: 10.3389/fpsyg.2014.01473
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and physiological effects of an acute physical activity intervention in elementary school children

Abstract: The aim of the present study was to investigate the effects of an acute physical activity intervention that included cognitive engagement on executive functions and on cortisol level in young elementary school children. Half of the 104 participating children (6–8 years old) attended a 20-min sport sequence, which included cognitively engaging and playful forms of physical activity. The other half was assigned to a resting control condition. Individual differences in children's updating, inhibition, and shiftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
4
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 72 publications
2
110
4
6
Order By: Relevance
“…Flanker Fish demanded inhibition, working memory, and cognitive flexibility to control attentional processing because children had to pay special attention to some features of the stimuli while inhibiting others and had to flexibly switch between game rules (Jäger, Schmidt, Conzelmann, & Roebers, 2014;Röthlisberger, Neuenschwander, Cimeli, Michel, & Roebers, 2012;Rueda, Posner, & Rothbart, 2005). The Hearts & Flowers task assessed behavioral control.…”
Section: Executive Functionsmentioning
confidence: 99%
“…Flanker Fish demanded inhibition, working memory, and cognitive flexibility to control attentional processing because children had to pay special attention to some features of the stimuli while inhibiting others and had to flexibly switch between game rules (Jäger, Schmidt, Conzelmann, & Roebers, 2014;Röthlisberger, Neuenschwander, Cimeli, Michel, & Roebers, 2012;Rueda, Posner, & Rothbart, 2005). The Hearts & Flowers task assessed behavioral control.…”
Section: Executive Functionsmentioning
confidence: 99%
“…However, no significant acute effects of the intervention on updating and shifting performance were found. The results showed no significant intervention effect on inhibition after 40 min of cognitively engaging physical activity [3]. In contrast, Schmidt et al [6] examined 90 fifth-grade students' attention and concentration in revised d2 test before, immediately after, and 90 min after students' participating in 45-min coordinated, aerobic PA (experimental condition) compared to the control students who were taking a regular 45-min academic lesson.…”
Section: Introductionmentioning
confidence: 95%
“…To address this critical issue, investigating the acute effects of PA on increasing attention and concentration in school-aged children has been of great interest in school settings. Empirical studies have examined the acute effects of a single bout of different types, durations, and intensities of PA on attention and concentration performance in school-aged children [1][2][3][4][5][6][7][8][9][10]. In a systematic review of 12 studies in acute effects of a single bout of PA on children's attention in the laboratory and the school settings, four out of seven studies showed that aerobic PA was positively associated with attention and concentration [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have proved that children with ADHD have some impairment in their social and school life throughout development such as inattention, hyperactivity, anxiety and cognitive functions (Katja et al 2014). Children with ADHD also made more mistakes in recognizing all types of emotional and neutral expression (Rommel et al 2015).…”
Section: Introductionmentioning
confidence: 99%